Effect of wind induced on road accident along east coast expressway (ECE) - Norain , Md Yusof (2012)
In becoming a develop country, Malaysia government had built infrastructure including new highway for easy commute. Hence of that, East Coast Expressway (ECE) was build from Kuala Lumpur to Kuantan. This expressway was built through roughness of Land Use and Land Cover (LULC), terrain and topography. From this situation will made cross wind phenomena occurred along that expressway. Consequently, road accident could be happen due to the phenomena of cross wind. Therefore, in this thesis terrain database along East Coast Expressway was establish and relationship slope topographic factor and wind speed was derived. Furthermore, access possibility of the accident prone location due to wind speed induced were identified. The GIS technique was used to establish database of study area and analysis information of topographic effect. The database demonstrates the system analyze in spatial analysis to obtain variation of slope along that area. Indirectly, this technique has enabled GIS database showing the system analysis for the effect of topographic variation in slope was established. In conclusion, the objective prove successful in the relation between data information and slope topographic effect of that area. Therefore, the results for this study can be made as a guideline for road construction and improvement in safety of the road users.